Role of Multivalency and Antigenic Threshold in Generating Protective Antibody Responses - Slifka, Mark K.; Amanna, Ian J. (Frontiers in Immunology, 2019)
Vaccines play a vital role in protecting our communities against infectious disease. Unfortunately, some vaccines provide only partial protection or in some cases vaccine-mediated immunity may wane rapidly, resulting in either increased susceptibility to that disease or a requirement for more booster vaccinations in order to maintain immunity above a protective level. The durability of antibody responses after infection or vaccination appears to be intrinsically determined by the structural biology of the antigen, with multivalent protein antigens often providing more long-lived immunity than monovalent antigens. This forms the basis for the Imprinted Lifespan model describing the differential survival of long-lived plasma cell populations. There are, however, exceptions to this rule with examples of highly attenuated live virus vaccines that are rapidly cleared and elicit only short-lived immunity despite the expression of multivalent surface epitopes. These exceptions have led to the concept that multivalency alone may not reliably determine the duration of protective humoral immune responses unless a minimum number of long-lived plasma cells are generated by reaching an appropriate antigenic threshold of B cell stimulation. Examples of long-term and in some cases, potentially lifelong antibody responses following immunization against human papilloma virus (HPV), Japanese encephalitis virus (JEV), Hepatitis B virus (HBV), and Hepatitis A virus (HAV) provide several lessons in understanding durable serological memory in human subjects. Moreover, studies involving influenza vaccination provide the unique opportunity to compare the durability of hemagglutinin (HA)-specific antibody titers mounted in response to antigenically repetitive whole virus (i.e., multivalent HA), or detergent-disrupted “split” virus, in comparison to the long-term immune responses induced by natural influenza infection. Here, we discuss the underlying mechanisms that may be associated with the induction of protective immunity by long-lived plasma cells and their importance in future vaccine design.